Preliminary Study of the Performance of a Bulb Heat-Based Dryer with Curly Chilli (Capsicum Annum L.) - muh yamin; Mujibu Rahman; Farida Aryani; Edy Wibowo Kurniawan; M. Atta Bary; Ahmad Zamroni; Adnan Putra Pratama; Mika Debora Br Barus; Hamka; Andi Giantoro (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Along with the development of industry and the increase in population, the need for chilies has also increased. This shows that more than half of the chilies that have been harvested have the potential to be wasted or not utilized optimally. So the dryer designed and made is a type of bulb heat-based dryer, namely a chili dryer that can use heat energy from the light rays of the bulb. With this dryer, it is hoped that there will be an increase in production capacity. Apart from that, the product obtained will be of good quality, namely having relatively clean chili quality. The research design used in this research is to use one treatment, namely for 10 hours from 08:00-18:00 and testing the specified parameters at a time interval of 120 minutes. In this research, the method used was an average calculation with one treatment repeated 3 times, symbolized P1= chili product 1, P2= chili product 2, P3= chili product 3. Bulb heat-based dryers can work well according to their use. This tool produces an average temperature of 52.44°C, and the highest temperature reaches 60°C. The capacity of this bulb heat-based dryer has 6 shelves and can accommodate 4,800 g of chili, with each shelf able to accommodate 800 g of chili.. Based on tests on the parameters that have been carried out, the average water content in chilies is 57.3354%. This result is still very high compared to the SNI for the water content in dried chilies of 11%.